CircAGK regulates high dihydrotestosterone‐induced apoptosis in DPCs through the miR‐3180‐5p/BAX axis. Issue 2 (6th January 2023) - Wei, Hanxiao; Yang, Shuai; Yi, Tian; Xu, Xiaoyu; Liu, Chang; Shen, Caiqi; Guo, Yanping; Li, Qiang; Jin, Peisheng
Abstract: The incidence of androgen alopecia (AGA), also known as seborrheic alopecia, has surged in recent years, and onset is occurring at younger ages. Dermal papilla cells (DPCs) are key to maintaining hair cycling, and apoptosis‐driven processes in DPCs are closely related to hair follicle regeneration. Circular RNAs (circRNAs) are widely present in the human body and are closely related to the occurrence and development of many diseases. Currently, the biological functions of circRNAs in AGA are largely unknown. Whole‐transcriptome sequencing was used to screen differential circRNA expression profiles between AGA patients and non‐AGA patients. We found that hsa_circ_0002980 (circAGK) was significantly highly expressed in the AGA group. CircAGK promoted DPC apoptosis in the presence of high dihydrotestosterone (DHT) (15 nmol/L). By regulating the miR‐3180‐5p/BAX axis, circAGK promotes DPC apoptosis in a high DHT environment in vitro and inhibits hair growth in AGA mice in vivo, indicating that circAGK is a potential target for the clinical treatment of AGA.